1957
DOI: 10.1111/j.1476-5381.1957.tb00131.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Edrophonium (Tensilon) and Acetylcholine at the Motor End‐plate

Abstract: The effect of edrophonium (3-hydroxy-phenyl-dimethylethylammonium chloride) on the motor end-plate and its interaction with acetylcholine and carbachol has been investigated. Use was made of intracellular recording of membrane potential and of ionophoretic micro-application of drugs from single and twin-pipettes.Small doses of edrophonium potentiate the depolarizing effect of acetylcholine, but not that of carbachol. This action can be observed with doses of edrophonium which have no depolarizing effect by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

1958
1958
1989
1989

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 10 publications
4
12
1
Order By: Relevance
“…Similar results were obtained with edrophonium (Tensilon: 3-hydroxyphenyldimethylethyl-ammonium chloride, Roche Products Ltd.), which is structurally related to prostigmine and has a similar anticholinesterase activity (Randall, 1950;Nastuk & Alexander, 1954;Katz & Thesleff, 1957). When administered intravenously this drug has no effect on Renshaw cells.…”
Section: Anticholinesterasessupporting
confidence: 65%
See 1 more Smart Citation
“…Similar results were obtained with edrophonium (Tensilon: 3-hydroxyphenyldimethylethyl-ammonium chloride, Roche Products Ltd.), which is structurally related to prostigmine and has a similar anticholinesterase activity (Randall, 1950;Nastuk & Alexander, 1954;Katz & Thesleff, 1957). When administered intravenously this drug has no effect on Renshaw cells.…”
Section: Anticholinesterasessupporting
confidence: 65%
“…However, the present series of experiments does not exclude the possibility that these drugs also have a depolarizing action (cf. Katz & Thesleff, 1957).…”
Section: Discussionmentioning
confidence: 99%
“…190 msec. These times are quite similar to those reported for the time course of action of edrophonium at the junctional membrane of frog muscle fibres by Katz & Thesleff (1957c (Nastuk & Alexander, 1954; Katz & Thesleff, 1957 c) could be demonstratedl at these sites with relatively large doses (Fig. 10 C).…”
Section: -2supporting
confidence: 89%
“…its effect is to inhibit the response to ACh and to produce a slight membrane depolarization (upper record). The general view is that the main action of edrophonium is inhibition of cholinesterase (Smith, Cohen, Pelikan & Unna, 1952;Nastuk & Alexander, 1954;Katz & Thesleff, 1957b); hence the absence of ACh potentiation indicates that the membrane is, in a practical sense, devoid of cholinesterase. Electrical excitability It has been suggested that, unlike the rest of the muscle membrane, the ACh receptors are not excitable by electrical stimulation (del Castillo & Katz, 1954).…”
Section: Supersensitivity In Denervated Musclementioning
confidence: 99%